2019
DOI: 10.1016/j.nicl.2019.101934
|View full text |Cite
|
Sign up to set email alerts
|

MRI cortical feature of bulbar impairment in patients with amyotrophic lateral sclerosis

Abstract: The decline of voluntary bulbar functions such as speech and swallowing are among the clinical manifestations of amyotrophic lateral sclerosis (ALS) influencing a worst prognosis. Differential diagnosis between the contribution of upper motor neuron (UMN) and lower motor neuron degeneration to the bulbar impairment is often hard. Thinning and T2* hypointensity of the primary motor cortex have been recently suggested as possible MRI markers of UMN impairment in ALS patients, but little research has purposely ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…Two previous QSM studies, using either a voxel‐based approach or a regional analysis along the posterior and precentral gyri, found an increase of iron deposition levels within the motor cortex of ALS patients, in comparison to either HCs 8 or patients with ASL mimics and non‐motor neuron symptoms 13 . In addition, the study of Donatelli et al., 14 which specifically targeted the orofacial portion of the primary motor cortex, also reported that the hypointensity of T2* signal and the corresponding higher susceptibility values, albeit non‐quantitatively, had significant discriminative power in diagnosing ALS with functional bulbar impairment. Similarly, the recent study of Conte et al 11 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Two previous QSM studies, using either a voxel‐based approach or a regional analysis along the posterior and precentral gyri, found an increase of iron deposition levels within the motor cortex of ALS patients, in comparison to either HCs 8 or patients with ASL mimics and non‐motor neuron symptoms 13 . In addition, the study of Donatelli et al., 14 which specifically targeted the orofacial portion of the primary motor cortex, also reported that the hypointensity of T2* signal and the corresponding higher susceptibility values, albeit non‐quantitatively, had significant discriminative power in diagnosing ALS with functional bulbar impairment. Similarly, the recent study of Conte et al 11 .…”
Section: Discussionmentioning
confidence: 91%
“…The development of advanced MRI techniques has allowed the proliferation of quantitative MRI (qMRI) markers, MRI‐derived measures that can be calibrated to standard physical units, whose diagnostic potential is yet to be fully investigated in the context of clinical MRI studies on the ALS pathology. For example, the involvement of gray matter (GM) structures in ALS neurodegeneration has been extensively studied using quantitative MRI markers, not only as morphometric indices of GM atrophy, but also as biophysical surrogates of structural and metabolic tissue properties, such as iron deposition 8–18 and cerebral perfusion 19–21 …”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the orofacial region of the primary motor cortex was investigated in relation to bulbar onset of ALS presentation. Magnetic susceptibility was significantly higher in those with marked T2 * hypointensity in the deep layer of orofacial region of the motor cortex, which was predominantly observed in patients with bulbar-onset disease (Donatelli et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…To test for these assumptions, one could perform longitudinal sampling with our tool to track tongue kinematic features with disease progression. Accurately quantifying bulbar dysfunction is further necessary to identify corresponding brain changes to the bulbar area of M1 by using neuroimaging methods (7,28). In addition, our measure could be used to track tongue movement training success to improve outcomes in dysphagia, as previously demonstrated with specialized equipment to measure tongue pressure in patients following acquired brain injury and stroke (4).…”
Section: Discussionmentioning
confidence: 96%